Implementasi K-Shortest Path Routing pada Jaringan Software Defined Network - Romy Dwi Andika Manullang; Widhi Yahya; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Software Defined Network (SDN) is a network modeling separating control plane and data plane. Network routing is part of SDN that give interest for the research. The most commonly used routing algorithm today is the single path routing algorithm. This algorithm uses only one path as the data transmission medium. This will reduced network performance known as network congestion. In this study we implemented Yen K-Shortest Path as routing algorithm. These algorithm will search for as many K lines as the data transmission medium. The Yen K-shortest path algorithm will minimize network congestion. These algorithms has been implemented using Mininet emulator and Ryu controller in two topology. The tests performed to measure the performance of the algorithm include convergence time, throughput, packet loss. The data obtained in the test using the Yen K-Shortest Path algorithm compared to data obtained using Dijkstra algorithm with the same test method. And there is a test to see the success of the algorithm for using more than one path on multipath testing. In the convergence time test, the Yen K-Shortest Path algorithm gets an average of 0.01962 seconds for the first topology, and 0.02409 seconds for the second topology. Based on the results of throughput testing, the Yen K-Shortest Path algorithm outperformed Dijkstra's algorithm with the highest throughput increase reaching 176.01% larger. For packet loss test results, Yen K-Shortest Path is also superior because it has fewer packet loss than Dijkstra algorithm.